2015
DOI: 10.3141/2494-06
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analysis of a Smartphone-Based Travel Survey in Singapore

Abstract: The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…However, we have argued that the automatic trip detection itself can also show a bias, which can be corrected for by a recall survey. Earlier smartphone studies that require user validation involve filling in missing information and amending incorrectly inferred data about, for example, trip purpose and modes of travel used (e.g., Safi et al, 2016;Zhao et al, 2015), but to our knowledge, respondents could not add undetected trips. Note from Safi et al (2016) we can derive an observed trip rate of 4.4 trips per person per day (1,873 recorded trips for 424 travel days according to their Table 3) for their sample in New Zealand, which is quite comparable with our result for The Netherlands.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we have argued that the automatic trip detection itself can also show a bias, which can be corrected for by a recall survey. Earlier smartphone studies that require user validation involve filling in missing information and amending incorrectly inferred data about, for example, trip purpose and modes of travel used (e.g., Safi et al, 2016;Zhao et al, 2015), but to our knowledge, respondents could not add undetected trips. Note from Safi et al (2016) we can derive an observed trip rate of 4.4 trips per person per day (1,873 recorded trips for 424 travel days according to their Table 3) for their sample in New Zealand, which is quite comparable with our result for The Netherlands.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, many smartphone apps using GPS and GSM have been developed to provide users with feedback on their travel behavior. The use of smartphones as data collection tools to supplement or replace traditional travel surveys has been the subject of several studies, in the United States (Reddy et al, 2010), Austria (Nitsche et al, 2014), Sweden (Prelipcean et al, 2014), Shanghai, China (Xiao et al 2015), Singapore (Zhao et al, 2015), and New Zealand (Safi et al, 2016). However, except the Future Mobility Sensing pilots in Singapore with almost 800 users participating for at least 14 days, existing smartphone-based studies have been limited in terms of sample sizes and the number of observed trip legs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the apparent types of data are (i) the type of passenger, the time to departure, the presence of luggage and walking in groups in public transport facilities, (ii) the points of pedestrians' interest in museums and the attractivity of these points, (iii) opening hours of shops and restaurants in commercial centers, (iv) concert schedules and toilets' locations in music festivals, (v) pollution and noise levels experienced by pedestrians in urban streets, etc. To collect the mentioned characteristics various recall methods may be used, including paper-based surveys distributed to individuals (Bachu et al, 2001;Kalakou et al, 2014), smartphone-based applications (Ohmori et al, 2005;Cottrill et al, 2013;Ball et al, 2014;Zhao et al, 2015), and webbased methods (Bohte and Maat, 2009).…”
Section: Data Requirementsmentioning
confidence: 99%